Individual Variability in the Semantic Processing of English Compound Words - Schmidtke, Daniel; Van Dyke, J. A.; Kuperman, Victor (American Psychological Association, 2018)
Semantic transparency effects during compound word recognition provide critical insight into the organization of semantic knowledge and the nature of semantic processing. The past 25 years of psycholinguistic research on compound semantic transparency has produced discrepant effects, leaving the existence and nature of its influence unresolved. In the present study, we examined the influence of semantic transparency and individual reading experience on eye-movement behaviour during sentence reading. Eye movement data were collected from 138 non-college-bound 16-26 year-old speakers of English in a sentence reading task representing a total of 455 different compound words. Measures of individual differences in reading experience were collected from the same participants, and consisted of standardized assessments of exposure to printed materials, vocabulary size and word recognition skill. Statistical analyses revealed facilitatory effects of both Modifier-Compound and Head-Compound transparency throughout the eye-movement record. Moreover, the study reports interactions between Head-Compound transparency and measures of reading experience. Readers with a small amount exposure to printed materials and a limited vocabulary size exhibited slower processing in late eye-movement measures when reading highly transparent compounds relative to opaque compounds. The opposite effect was observed for readers with a relatively large amount of exposure to printed materials and a relatively bigger vocabulary size, such that highly transparent compounds facilitated lexical processing. To account for the results, the authors posit a trade-off between two cognitive mechanisms which is modulated by individual reading experience., i.e., the benefit of semantic co-activation of closely related concepts, and the cost of discriminating between those concepts.
Keywords: Morphology; Semantic transparency; Compound word recognition; Eye-tracking; Individual differences; Naive discriminative learning; Eye-movements